Inclusive unions in a dualised labour market? The challenge of organising labour market policy and social protection for labour market outsiders - Niccolo Durazzi (London School of Economics and Political Science (LSE), European Institute, 2015)
Dynamics of labour market dualisation have affected most Western European countries over the last two decades and trade unions have been often seen as conservative institutions protecting the interests of their core constituencies and as such contributing to labour market dualisation. However, empirical evidence from Italy shows that unions' stance towards atypical workers has been more inclusive than the literature expected, despite the conditions for pro-insider policies being firmly in place, and unions have emerged as important actors in the organisation of social protection for labour market outsiders. By analysing unions' strategies towards temporary agency workers in Italy through a disaggregated approach (i.e. focussing separately on salary and job protection; active labour market policies; and income protection), I reconcile the empirical observations that conflict with the theoretical expectations. I argue that unions have indeed put in place inclusive, yet selective, policies towards atypical workers and that unions' identity is a central explanatory variable to understand the puzzling coexistence of a dualised labour market and (selectively) inclusive unions. Through a disaggregated identity-bound analysis of unions' strategies, I shed new light on the complex relationship between labour market dualisation and the dualisation of social protection. In particular, findings suggest that paradoxically unions' strategies to counteract labour market dualisation may be furthering the insider-outsider divide in terms of social protection. I also suggest that a clearer analytical distinction between labour market dualisation and welfare dualisation is needed in future research and that the understanding of unions' strategies towards marginal workers would greatly benefit from a systematic disaggregated analysis of unions' agency.
Keywords: 330; trade unions; dualisation; interests; ideas; atypical work; Italy